Double skin facades (DSF) and building integrated photovoltaics (BIPV): A review of configurations and heat transfer characteristics - Agathokleous, Rafaela; Kalogirou, Soteris A. (My University, 2016)
This article presents the state of the knowledge on the thermal analysis of double skin facades with integrated photovoltaic (PV) panels called the Building Integrated Photovoltaics (BIPV) in terms of the published studies carried out on these systems. The idea of integration of the PV panels by replacing building elements, increase the prospects of the renewable energy systems. Taking also into account the need to use more renewable energy systems in buildings, the investigation of the BIPV systems to improve their performance is of a great importance. The literature studies are separated into experimental and theoretical for naturally ventilated systems and mechanically ventilated with external means e.g. fan use. It is concluded that most researchers studied the systems with mechanical ventilation rather than the systems with natural ventilation because the latter are more complex in terms of the air flow behaviour in the air duct. Additionally, various researchers proposed Nu number correlations and convective heat transfer correlation under several assumptions and conditions every time, for different range or Ra number which are presented and compared in this paper.
Keywords: BIPV; BIPV/T; DSSF; DSVF; PV; Solar façades